Hedging freight in futures markets - Florou, Aikaterini (Τμήμα Εμπορίου, Χρηματοοικονομικών και Ναυτιλίας, Σχολή Διοίκησης και Οικονομίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2019)
This thesis purpose is to analyze the freight hedging effectiveness in futures markets. We estimate the Hedge Ratio by using two different approaches. The first strategy is the naïve constant hedge ratio with the Least Squared regression analysis and the second strategy was the GARCH model, in which we estimate a time-varying hedge ratio
Keywords: Risk Management; Derivatives; Shipping; Options; Freight; Hedging effectiveness; Optimal Hedge ratio